The uneven effects of COVID-19 on the German restaurant and bar industry - Verfürth, Philip; Neise, Thomas; Franz, Martin; Sohns, Franziska (ERDKUNDE, 2022)
The COVID-19 crisis in the restaurant and bar industry is affecting an industry that has been under significant pressure before. Using the concept of organizational resilience from a spatial perspective, we analyze how individual/company factors and regional factors influence owner’s assessment of resilience in the German restaurant and bar industry. Findings from an online survey with 445 owners and managers and 46 qualitative interviews in Germany show that enterprises in peripheral locations are perceived as more resilient. Similarly, the age of the respondents, the ownership of property and the provision of delivery and takeaway service play a positive role in enterprises being seen as resilient, while, owner-managed enterprises, financing by loans or credit, and lower ex-ante sales reduce the likelihood of the assessment of resilience. Overall, the study contributes to the evolving strand of research that aims to analyze the resilience of enterprises from a spatial perspective.